Factors Related to the Participation of Mothers’ Toddlers in the Stunting Prevention Program at Sicanang Health Center Medan City - Sri Hajijah Purba; Ida Yustina; Etti Sudaryati (Randwick International of Social Science Journal, 2023)
One of the wholesome issues in the world nowadays is the issue of hindering which is being experienced by toddlers, especially in developing and poor countries. Malnutrition during the growth and development of toddlers will hinder their physical development, increase morbidity, hinder children's mental development, and can cause death. Based on data of Medan City Health Office or Dinas Kesehatan Kota Medan, stunting cases in 2022 as of August reached 555 cases. The sub-district with the highest stunting cases was in Secanang Sub-District with the number of verified cases as of August 2022 of 61 (6.40%) cases of stunting under five. This study aims to analyze the Factors Associated with the Participation of Mothers under Toddlers in the Stunting Prevention Program in the Working Area of the Sicanang Health Center, Medan City. This research is a quantitative analytic survey research with a cross sectional design. The sample used amounted to 100 people. Data analysis used univariate and bivariate analysis. The outcomes about appeared that the related factors were Eagerness (p=0.018), Capacity (p=0.026), Opportunity (p=0.037) and Social Back (p=0.001) with the Cooperation of Moms Little children within the Stunting Avoidance Program within the Work Range of the Sicanang City Wellbeing Center Medan.Suggestions for this research are that the stunting prevention program officers are expected to conduct education about the stunting prevention program for mothers of toddlers who have stunted children or not, so that it can be prevented and treated early so that stunting rates can be reduced and nutrition can be improved from an early age. And also stunting prevention program officers can make improvements to the program by conducting socialization on how to prevent counseling in health-based community activities to coordinate with each other and have good communication.